1986
DOI: 10.1146/annurev.ne.09.030186.001005
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-Electrical Transduction in Insect Olfactory Receptors

Abstract: INTRODUCTIONInsect behavior can be controlled by a single odor compound or by a blend of a few components in an exact ratio of concentrations. These odor compounds or odor mixtures are called pheromones if used for intraspecific communication. Each of the pheromone components is perceived by a particular type of receptor cell that is specifically tuned to its "key compound" and may respond to single odor molecules by firing single nerve impulses. The entire response range of a receptor cell may cover many deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(74 citation statements)
references
References 66 publications
3
70
0
1
Order By: Relevance
“…This is particularly curious because there are typically two or three neurons present in each sensillum, all closely related, having derived from a common sensory mother cell (34). Furthermore, each neuron differs in its response to specific pheromone components (3,41,42). The staining of only one neuron per sensillum may indicate that Snmp-1 is a molecular marker of that sibling neuron, thus suggesting some unique role for that neuron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly curious because there are typically two or three neurons present in each sensillum, all closely related, having derived from a common sensory mother cell (34). Furthermore, each neuron differs in its response to specific pheromone components (3,41,42). The staining of only one neuron per sensillum may indicate that Snmp-1 is a molecular marker of that sibling neuron, thus suggesting some unique role for that neuron.…”
Section: Discussionmentioning
confidence: 99%
“…The antennae of silk moths are well known for their exquisite sensitivity to pheremonal odorants (1)(2)(3). Early reports demonstrated that the males of the wild silk moth Samia cynthia could locate a sex pheromone source over 2 miles away within several hours of their release (4).…”
mentioning
confidence: 99%
“…These sensilla are hollow cuticular structures containing the receptor cell sensory dendrites (cilia) bathed in a fluid, called the sensillum lymph. Pheromone molecules are thought to diffuse through the pore tubules in the cuticular wall and across the sensillum lymph to reach receptors located in the cilia (3)(4)(5).…”
mentioning
confidence: 99%
“…This finding and the protein's enormous 10 mM concentration in the sensillum lymph led to the suggestion that it serves to solubilize the extremely hydrophobic pheromone molecules (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…As examples, the human eye is able to count single photons [1], hair cells in the cat cochlea are able to detect displacements of the basilar membrane smaller than 10 −10 m [1], the olfactory system of the domesticated silk moth (Bombyx mori) can detect single molecules of pheromone [2], and thermal receptors in crotalid snakes are able to recognize the temperature difference of 0.003 o C [3]. All these systems share a simple design principle based on sensor array architectures; high sensitivity is achieved through the use of a large number of sensory receptors.…”
Section: Introductionmentioning
confidence: 99%